(untitled) (Sebha University Conference Proceedings, 2025)
This Paper presents modelling, simulation and flight testing of a quadrotor Unmanned Ariel Vehicle (UAV) Focus of this paper is to gain in-depth understanding of quadrotor dynamics to develop a simulator and a laboratory platform to facilitate future development of control algorithms. Quadrotor dynamics is modelled using Newton-Euler method. The model predicts the effects of the forces and torques generated by the four propellers on the quadrotor motion. Based on the Mathematical model, a quadrotor simulator was developed in MATLAB® Simulink, on which manually control Using joystick in Flight-Gear simulation environments to understand the Quadrotor behaviour in virtual reality. A Quadrotor platform will be developed composed of a Flight controller (KK-2) interfaced with several devices: power supply, receiving unit, BLDC-motor power boards, and the set of propellers.